Differences in the Asthma Treatment of Children Between Europe and Japan - Mitsuhiko Nambu, MD,PhD; Stephen Holgate, MD, FMedSci (World Allergy Organization Journal, 2009)
Background The aim of this study is to compare asthma controller therapy in children between Europe and Japan.Materials and Methods A questionnaire-based survey was conducted at the 2007 annual meeting of the European Respiratory Society held in Stockholm. In total, 120 answers were collected from European doctors. We divided Europe into 5 areas: South, West, North, East, and Central. The same survey was conducted at the 40th annual meeting of the Japanese Society of Pediatric Pulmonology. Forty-three answers were collected from Japanese doctors.Results Inhaled corticosteroids were used more frequently in Europe and antileukotrienes were used more frequently in Japan. There were also some differences in treatment in different areas of Europe.Conclusion This survey shows differences in the treatment of children with asthma in Europe and in Japan. European doctors prefer using inhaled corticosteroids, and Japanese doctors prefer using oral antileukotrienes. Because the number of the respondents is small and there may be some bias, further study on a large-scale for general clinicians providing medical care to asthma children is desirable. Keywords: asthma treatment, children, Europe, Japan, questionnaire-based survey